2015
DOI: 10.1073/pnas.1507312112
|View full text |Cite
|
Sign up to set email alerts
|

Bcl6 middle domain repressor function is required for T follicular helper cell differentiation and utilizes the corepressor MTA3

Abstract: T follicular helper (Tfh) cells are essential providers of help to B cells. The transcription factor B-cell CLL/lymphoma 6 (Bcl6) is a lineage-defining regulator of Tfh cells and germinal center B cells. In B cells, Bcl6 has the potential to recruit distinct transcriptional corepressors through its BTB domain or its poorly characterized middle domain (also known as RDII), but in Tfh cells the roles of the Bcl6 middle domain have yet to be clarified. Mimicked acetylation of the Bcl6 middle domain (K379Q) in CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…The KKYK motif also mediates direct interaction with metastasis-associated protein 3 (MTA3) [70], a subunit of the NuRD complex. Strikingly, mice harboring either the Bcl6 QQYQ or Bcl6 KKYQ mutation largely phenocopy Bcl6 KO mice [71, 72], suggesting that BCL6 acetylation serves as a molecular switch governing BCL6-mediated repression in vivo. The BCL6 RD2 also contains a PEST motif, which is phosphorylated by mitogen-activated protein kinase (MAPK) following B cell receptor (BCR) signaling [73].…”
Section: Zbtb Protein Molecular Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The KKYK motif also mediates direct interaction with metastasis-associated protein 3 (MTA3) [70], a subunit of the NuRD complex. Strikingly, mice harboring either the Bcl6 QQYQ or Bcl6 KKYQ mutation largely phenocopy Bcl6 KO mice [71, 72], suggesting that BCL6 acetylation serves as a molecular switch governing BCL6-mediated repression in vivo. The BCL6 RD2 also contains a PEST motif, which is phosphorylated by mitogen-activated protein kinase (MAPK) following B cell receptor (BCR) signaling [73].…”
Section: Zbtb Protein Molecular Mechanismsmentioning
confidence: 99%
“…Since T cell-specific Bcl6 inactivation also abrogates GC formation [108110], Bcl6 likely regulates GC formation through at least three distinct mechanisms: (1) induction of Tfh cell development; (2) initiation of pre-GCB cell migration to the follicle; and (3) support of GCB cell proliferation and survival. Notably, two groups independently showed that co-repressor recruitment via BCL6-BTB domain is necessary for GC development in vivo, although there remain discrepancies regarding the contribution of Tfhs to observed phenotypes [57, 71, 72, 113]. …”
Section: Zbtb Function In Hematopoietic Developmentmentioning
confidence: 99%
“…Each of these domains can associate with specific corepressor complexes in B cells and macrophages. Both the RD2 domain and BCL6 BTB domain have been shown to be important in Tfh cell function in vivo [44][45][46]. We found that RI-BPI, a peptide inhibitor that can disrupt the association of the BCL6 BTB domain with its corepressors, was able to up-regulate Tfh ISG expression, suggesting the BCL6 BTB domain is critically important in suppressing ISG expression in Tfh cells.…”
Section: Discussionmentioning
confidence: 74%
“…HIC1 acetylation on K314 in the MKHEP SUMOylation/acetylation motif negatively regulates its interaction with MTA1, whereas its SUMOylation favors it, notably in the DNA damage response (40,59). BCL6 acetylation on K379 in the KKYK motif abrogates its ability to interact with MTA3, which is a major repression mechanism controlling germinal center B-cell differentiation (60)(61)(62) as well as CD4 ϩ T-cell fate and function (63). Although our studies have been focused on BCL11B, it is tempting to speculate that similar PTMs could be identified in other MSRRKQ-containing nuclear proteins.…”
Section: Discussionmentioning
confidence: 99%